Choosing and differentiating instructions in language teaching - Khamzaeva Mukaddas Fayzullaevna (Academia One, 2024)
Teaching a foreign language involves learning how to use the language and engaging in conversation. One must practice and gain expertise to utilize the language within and outside the classroom. Most students may find it challenging for various reasons, such as a lack of interaction during the learning process, tasks emphasizing knowledge acquisition over language proficiency, an unbalanced focus on receptive and productive skills, and personality factors. They will, therefore, probably be unable to communicate through language effectively. However, the Communicative Language Teaching (CLT) method offers a promising solution, emphasizing interaction, authentic materials, and the integration of receptive and productive skills. Bringing the outside world into the classroom addresses these challenges and enhances the learning experience for both students and educators
Keywords: Interact; authentic materials; receptive skills; productive skills